2019
DOI: 10.1186/s11671-019-3154-0
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Cadmium Ions from an Aqueous Solution on a Highly Stable Dopamine-Modified Magnetic Nano-Adsorbent

Abstract: Magnetic nanomaterials were functionalized with dopamine hydrochloride as the functional reagent to afford a core–shell-type Fe3O4 modified with polydopamine (Fe3O4@PDA) composite, which was used for the adsorption of cadmium ions from an aqueous solution. In addition, the effects of environmental factors on the adsorption capacity were investigated. Furthermore, the adsorption kinetics, isotherm, and thermodynamics of the adsorbents were discussed. Results revealed that the adsorption of cadmium by Fe3O4@PDA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
53
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 69 publications
(54 reference statements)
9
53
1
Order By: Relevance
“…Similar results were reported for Pb 2+ and Cd 2+ biosorption by magnetic Bauhinuia purpurea pods [ 10 ]. Lei et al [ 25 ] revealed that Fe 3 O 4 magnetic nanoparticles exhibited a more rapid adsorption rate in the initial phase of Cd 2+ adsorption (before 90 min) and then, similarly as in our experiments, the adsorption rate tends to be flat. The observed distinctions in the kinetics profiles of organic dye and metal ions are caused by (1) different mechanisms of Co 2+ and TT adsorption, and (2) the distinct affinity of Co 2+ and thioflavin T to binding sites on magnetically responsive biosorbent.…”
Section: Resultssupporting
confidence: 88%
“…Similar results were reported for Pb 2+ and Cd 2+ biosorption by magnetic Bauhinuia purpurea pods [ 10 ]. Lei et al [ 25 ] revealed that Fe 3 O 4 magnetic nanoparticles exhibited a more rapid adsorption rate in the initial phase of Cd 2+ adsorption (before 90 min) and then, similarly as in our experiments, the adsorption rate tends to be flat. The observed distinctions in the kinetics profiles of organic dye and metal ions are caused by (1) different mechanisms of Co 2+ and TT adsorption, and (2) the distinct affinity of Co 2+ and thioflavin T to binding sites on magnetically responsive biosorbent.…”
Section: Resultssupporting
confidence: 88%
“…In addition, a high initial metal ion concentration enhances diffusion from the solution to the adsorbent's active sites i.e. there is an increase in the diffusion gradient leading to an increase in the mass transfer process (Lei et al, 2019). In general, our experimental results elucidate that there is a positive correlation between the initial metal ion concentration and adsorption capacity.…”
Section: Effect Of Initial Sorbate Concentrationmentioning
confidence: 49%
“…They attributed this observation to a decrease in binding sites with an increase in initial metal ion concentration due to saturation of the binding sites. El-Naggar et al (2019) observed a similar trend when they employed a Kaolinite/Smectite natural composite adsorbent to study the removal of Pb 2þ ions from wastewater, using different concentrations of Pb 2þ ions ranging from 125 to 500 mg/L Lei et al (2019) also observed a similar trend when using dopamine-modified magnetic nano-adsorbents to adsorb Cd 2þ ions from an aqueous solution.…”
Section: Effect Of Initial Sorbate Concentrationmentioning
confidence: 75%
See 1 more Smart Citation
“…Researchers oen modify the surface of materials to improve their acid/base resistance, adsorption, and selectivity. [31][32][33] The adsorption interaction between metal ions and functional groups mainly include ionic bonds and covalent bonds. 34 To enhance the adsorption capacity of ions, we designed a magnetic adsorbent with terpyridyl groups.…”
Section: Introductionmentioning
confidence: 99%